Social cognition in the course of psychosis and its correlation with biomarkers in a male cohort. Issue 2 (4th March 2018) - Ntouros, Evangelos; Karanikas, Evangelos; Floros, Georgios; Andreou, Christina; Tsoura, Aikaterini; Garyfallos, Georgios; Bozikas, Vasilios P.
ABSTRACT: Introduction: Patients diagnosed with schizophrenia display deficits in Theory of Mind (ToM) and Emotion Perception (EP) even before the appearance of full-blown symptomatology. Methods: We evaluated ToM and EP in a male cohort consisting of 25 First Episode Psychosis (FEP) and 16 relapsed schizophrenic patients (CHRON) compared to 12 subjects in Ultra-high Risk (UHR) and 23 healthy controls (CTR). Furthermore, we measured the levels of Cortisol, Insulin like Growth Factor (IGF-1), TNF-a, TNF-b and several interleukins as potential biomarkers. Results: Deficits in EP and ToM were found in FEP, CHRON patients and UHR subjects compared to CTR. The impairments in these two domains seem to follow different patterns in the course of psychosis. EP was more impaired in subjects with a longer history of symptomatology whereas there was no statistically significant difference regarding ToM. On the other hand IL-4 was the only biomarker correlated to ToM and EP scores in two different samples of our study. Conclusion: Social Cognition (SC) domains are impaired in patients with psychosis as well as in UHR subjects compared to healthy controls. There are differences in the progress of ToM and EP deficits in the course of psychosis. Interleukins as IL-4 could correlate to SC.